Exercise capacity, quality of life, and resilience after repair of tetralogy of Fallot: a cross-sectional study of patients operated between 1964 and 2009. (18th February 2013) - Frigiola, Alessandra; Bull, Catherine; Wray, Jo
Abstract: Introduction: Patients with repaired tetralogy of Fallot have good long-term survival but less is known about the subjectively assessed quality of life or objectively measured functional status of those who have not required subsequent pulmonary valve replacement. We assessed these parameters in a group of children and adults free from pulmonary valve replacement after tetralogy of Fallot repair. Methods and results: A random sample of 50 subjects – 16 children and 34 adults, aged 4.1–56.7 years – who had undergone tetralogy of Fallot repair and were free from subsequent pulmonary valve replacement underwent cardiopulmonary exercise testing and completed standardised questionnaires assessing health-related quality of life and resilience. Patients were generally asymptomatic (median New York Heart Association class = I). Exercise capacity was within two standard deviations of normal for most children and adults (mean z VO2max : 0.20 ± 1.5; mean z VE/VCO2 : −0.9 ± 1.3). Children reported a total health-related quality of life score similar to healthy norms (78 ± 10 versus 84 ± 1, p = 0.73). Adult survivors also reported quality of life scores comparable to healthy norms. Resilience was highly correlated with all domains of health-related quality of life (r = 0.713, p < 0.0001). Conclusions: Patients who have undergone tetralogy of Fallot repair in childhood and have not required pulmonary valve replacement have a good long-term health-related quality of life. The finding that patients with greater resilience had better health-related quality of life suggests that it may be beneficial to implement interventions to foster resilience.